REFORMASI KURIKULUM PENDIDIKAN DASAR: ANTARA HARAPAN DAN REALITA DARI K 13 MENUJU KURIKULUM MERDEKA DI SEKOLAH MI - Anaphaliza Davi Farhani; Naeli Tamami; Nur Hidayah Nasution (Jurnal Manajemen Pendidikan, 2026)
Objective: Curriculum reform in Indonesia has shifted significantly from the 2013 Curriculum (K-13) to the Merdeka Curriculum, which aims to provide learning flexibility and character development. However, implementing this conceptual framework creates a gap between expectations and reality in primary education, particularly in Madrasah Ibtidaiyah (MI). This study aims to analyze the challenges and readiness of MI during this curriculum transition. Using a descriptive qualitative approach with a case study design, data were gathered through interviews, observations, and documentation. The results indicate a notable discrepancy between ideal expectations and field realities. While the Merdeka Curriculum is expected to reduce administrative burdens and center on students, MI teachers face major obstacles. These include limited formal training, difficulties in designing differentiated lesson plans, and adaptation challenges with digital grading applications. This study concludes that the transition from K-13 to the Merdeka Curriculum in MI is still in a challenging phase that requires intensive assistance and sustainable guidance rather than a simple administrative change.